Survey self esteem and its relevant factors among high school students - Maryam Babaei; Reihane Fadakar Soghe; Farzaneh Sheikhol-Eslami; Ehsan Kazemnejad Leili (Journal of Holistic Nursing and Midwifery)
Abstract Introduction: Self-esteem is one of the necessities of human life and most professionals consider it as a major factor in social and emotional adjustment. Low self-esteem in students causes academic failure, loneliness, drug abuse, away from reality and self-destructive behaviors. Objective: This study aimed to determine the level of self-esteem and its related factors in high school students in Rasht city. Methods: In this descriptive-analytical study, 489 high school students in Rasht city were randomly chosen and surveyed. Method of data collection was a questionnaire consisting of two parts. Part one included standard questionnaire of Cooper Smith Self-esteem Inventory which surveyed 4 domains (general, education, familial and social) and second part was a researcher made questionnaire covering related factors to self esteem including two parts of personal and familial factors (age, gender, height, weight, order of birth, grade level, major, last year s Great Point Average, religious activities, physical and emotional illness, apparent problems, number of family members, education, occupation and age of parents, family monthly income, place and condition of living). For data analysis descriptive statistics and Kruskal-Wallis and Mann-Whitney U tests were used. Results: Findings indicated that only 37.8% of cases studied had good self-esteem. Also a significant relationship was shown between self-esteem, sex P< 0.04), bound to religious practice (p=0.0001) and family monthly income (p<0.006). Conclusion: Considering the low level of self esteem among most cases, more attention of teachers and parents is necessary to promote adolescents self esteem